Latin American integration, nationalism and geopolitical conceptions: the thoughts of Ítalo Argentino Luder in the 1970s and 1980s (Quinto Sol, 2022)
In this work, the intellectual production of one of the prominent political actors within Peronism in the 1970s and 1980s was analyzed: Ítalo Argentino Luder. Specifically, its development proposal and Argentine foreign policy were examined, evidencing elements typical of the irredentist national territorialist current in coexistence with an integrationist profile of the Latin American space. The hypothesis that guides this article is that Ítalo Luder, through his speeches and publications, was forging a national development project framed within the Latin American space based on the peaceful coexistence of nations that responds to his non-confrontational geopolitical conceptions.
Keywords: integration; nationalism; geopolitical conceptions; development